2021
DOI: 10.15694/mep.2021.000126.1
|View full text |Cite
|
Sign up to set email alerts
|

Learning through lived experience: An educational tool to improve health professionals’ insight into the perspectives of patients

Abstract: IntroductionHealthcare professionals tried to adhere to a chronically ill patient's daily regimen for two weeks as an educational tool to increase their insight into patients' perspectives. MethodsParticipants responded to a baseline-, daily-and evaluating questionnaire. The primary outcome: on a scale from 0-10, how much insight do you have into the perspective of patients? Associations between baseline-and final data were established using paired T-tests. Results108 Participants were included and complete da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Increasingly patients are involved in medical education and new initiatives are developed in which students learn about patient perspectives from patients themselves. For instance by interviewing patients with chronic conditions [ 7 ], following a patient’s daily regime [ 8 ], home visiting families of children with special needs [ 9 ], or filming patients with serious chronic illness in their daily lives [ 10 ]. However, reviews on patient involvement have demonstrated that little is known on how students learn from patients [ 11 12 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly patients are involved in medical education and new initiatives are developed in which students learn about patient perspectives from patients themselves. For instance by interviewing patients with chronic conditions [ 7 ], following a patient’s daily regime [ 8 ], home visiting families of children with special needs [ 9 ], or filming patients with serious chronic illness in their daily lives [ 10 ]. However, reviews on patient involvement have demonstrated that little is known on how students learn from patients [ 11 12 13 ].…”
Section: Introductionmentioning
confidence: 99%